2020
DOI: 10.1093/mnras/staa3167
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the growing population of massive quiescent galaxies at cosmic noon

Abstract: We explore the buildup of quiescent galaxies using a sample of 28,469 massive (M⋆ ≥ 1011M⊙) galaxies at redshifts 1.5 < z < 3.0, drawn from a 17.5 deg2 area (0.33 Gpc3 comoving volume at these redshifts). This allows for a robust study of the quiescent fraction as a function of mass at 1.5 < z < 3.0 with a sample ∼40 times larger at log(M⋆/$\rm M_{\odot })\ge 11.5$ than previous studies. We derive the quiescent fraction using three methods: specific star-formation rate, distance fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(60 citation statements)
references
References 138 publications
5
54
1
Order By: Relevance
“…1 reveals that Illustris-1 galaxies are typically thicker and thus less susceptible to bar instability. In general, the TNG galaxies agree better with observational properties (Nelson et al 2018), except for overquenching (Angthopo et al 2020;Sherman et al 2020), which is most probably due to too strong kinetic feedback from active galactic nuclei, combined with high thresholds for the seed black hole mass and halo mass. This may be of concern in the case of galaxies of our class C, which may rid themselves of the gas too efficiently and form bars too easily.…”
Section: Discussionmentioning
confidence: 62%
“…1 reveals that Illustris-1 galaxies are typically thicker and thus less susceptible to bar instability. In general, the TNG galaxies agree better with observational properties (Nelson et al 2018), except for overquenching (Angthopo et al 2020;Sherman et al 2020), which is most probably due to too strong kinetic feedback from active galactic nuclei, combined with high thresholds for the seed black hole mass and halo mass. This may be of concern in the case of galaxies of our class C, which may rid themselves of the gas too efficiently and form bars too easily.…”
Section: Discussionmentioning
confidence: 62%
“…An often used SFR threshold for defining quiescence is 1 dex below the main sequence (see e.g., Morselli et al 2019;Donnari et al 2019;Sherman et al 2020) which we show for measurements in an aperture of 30 kpc in Figure 1 together with the Franx et al (2008) criterion sSFR < 0.3 × 𝐻 (𝑡) (see also Lotz et al 2021, in particular on a study in Magneticum), that is log(sSFR × yr) ≈ −10.0 at 𝑧 = 2.75. As the figure shows, in M3 the MS-based quiescence threshold is 0.3 dex lower than the Franx et al (2008) sSFR threshold over the full mass range.…”
Section: Selection Of Quiescent Galaxies In Simulationsmentioning
confidence: 52%
“…This fraction is consistent with the results of B19, who found that their emission-line sample only contained ∼ 30% of the galaxies with photometric redshifts between 1.90 < z < 2.35 in the 3D-HST catalog. While a subset of the photometric redshift sample is quiescent, the data of Sherman et al (2020) show that the quiescent fraction is not sufficient to explain the discrepancy. The B19 analysis also found strong trends with rest-frame near-IR continuum magnitude and dust content, where the fraction of emission-line galaxies fell to zero at bright magnitudes and large A V values.…”
Section: Calibrating the Sfr Relationmentioning
confidence: 94%